2018
DOI: 10.3390/ijms19103255
|View full text |Cite
|
Sign up to set email alerts
|

Detours to Replication: Functions of Specialized DNA Polymerases during Oncogene-induced Replication Stress

Abstract: Incomplete and low-fidelity genome duplication contribute to genomic instability and cancer development. Difficult-to-Replicate Sequences, or DiToRS, are natural impediments in the genome that require specialized DNA polymerases and repair pathways to complete and maintain faithful DNA synthesis. DiToRS include non B-DNA secondary structures formed by repetitive sequences, for example within chromosomal fragile sites and telomeres, which inhibit DNA replication under endogenous stress conditions. Oncogene acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 231 publications
(279 reference statements)
0
33
0
Order By: Relevance
“…( 84 , 133 ). Non-B DNA loci composed of repeats can pose an obstacle to DNA replicative polymerases, and the observed nucleotide substitution frequencies could reflect processing by low-fidelity, specialized DNA polymerases ( 65 , 66 , 134–136 ) gene conversion and increased DNA damage. Gene conversion is common at cruciform and slipped-strand structures ( 137 ), and could explain the decreased nucleotide substitution frequencies in repeat arms of inverted and direct repeats—particularly for fixed nucleotide substitutions, where multiple rounds of gene conversion might have taken place.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…( 84 , 133 ). Non-B DNA loci composed of repeats can pose an obstacle to DNA replicative polymerases, and the observed nucleotide substitution frequencies could reflect processing by low-fidelity, specialized DNA polymerases ( 65 , 66 , 134–136 ) gene conversion and increased DNA damage. Gene conversion is common at cruciform and slipped-strand structures ( 137 ), and could explain the decreased nucleotide substitution frequencies in repeat arms of inverted and direct repeats—particularly for fixed nucleotide substitutions, where multiple rounds of gene conversion might have taken place.…”
Section: Discussionmentioning
confidence: 99%
“…Replicative polymerases encounter many non-B DNA structures that act as natural impediments to DNA synthesis elongation. Specialized DNA polymerases associated with the replication fork, including Pols eta and kappa, perform highly efficient synthesis through non-B DNA structures (reviewed in ( 56 , 65 , 66 )), and can take over synthesis from stalled replicative polymerases ( 67 ). DNA damage-induced mutagenesis has been associated with non-B structure formation (reviewed in ( 68 )), and damage induced by reactive oxygen species is affected by the inherent structure and local sequence of DNA (reviewed in ( 69 )).…”
Section: Introductionmentioning
confidence: 99%
“…Further insights into the link between replication stress and CIN came from the discovery of the replication stress protection conferred by specialized polymerases that are able to replicate across noncanonical DNA and AT-rich sequences at difficult-to-replicate regions [105,106]. Notably, it was shown that the translesion synthesis DNA polymerase eta is recruited to specific CFSs during the S phase and promotes their timely replication [107].…”
Section: Mitotic Rescue From Replication Stressmentioning
confidence: 99%
“…Interestingly, non-B structured and difficult-to-replicate DNA regions, are present in eukaryotic genomes: Z-DNA, H-DNA triplex, cruciform, hairpins, and G- tetrads (Wickramasinghe et al, 2015 ; Tsao and Eckert, 2018 ; Stern et al, 2019 ). In mammals, Y-family polymerases have been implicated in replicating these particular regions (Eddy et al, 2014 , 2016 ; Wickramasinghe et al, 2015 ; Quinet et al, 2018 ; Tsao and Eckert, 2018 ). Moreover, a role in DNA replication origin has been recently described (Prorok et al, 2019 ).…”
Section: Dna Polymerases Families Overviewmentioning
confidence: 99%